EFFECT OF WATER REGIME ON GROWTH AND YIELD OF LETTUCE (LACTUCA SATIVA L.) - S. K. ACHARYA; Y. R. SHUKLA; P. C. KHATIK (The Bioscan, 2013)
Lettuce (Lactuca sativa L.) is one of the most important salad vegetables of the world due to its potential to return profit, nutritional value and production potential. Experiment was carried out in a naturally ventilated polyhouse erected at the experimental farm of the Department of Vegetable Science, Dr Y. S. Parmar University of Horticulture and Forestry, Nauni, Solan (H P) during 2009-10 and 2010-11. Twelve treatment combinations comprising of three depths of irrigation water (1.0, 1.5 and 2.0cm) and four irrigation intervals (4, 6, 8 and10 days) were replicated thrice in a randomized block design (factorial) having plot size of 1.80m X 1.80m with a spacing of 45 X 30cm. The observations were recorded on ten randomly selected plants on days to marketable maturity, gross head weight (g), number of non wrapper leaves, net head weight (g), heading (%) and yield/m2 (kg). Analysis of variance showed highly significant differences among different treatments for all the characters studied but treatment combination comprising of 1.5cm of irrigation water applied after 8 days was rated as the best combination for characters like yield, net head weight and number of non wrapper leaves followed by the treatment combination involving 1.5cm of irrigation water when applied after 6 days for characters like gross head weight and days to marketable maturity. About 21.50cm of irrigation water was consumed for producing 43.10 tonnes/ha yield with optimum water productivity of 2.00 tonnes/ha/cm in the treatment combination involving 1.5cm of irrigation water applied after 8 days interval.